A case of post-COVID Aspergillus fumigatus spondylodiscitis - Harafan, Abdulla; Adarsh; Arun; Shisham; Jipin; N. R., Fijad (International Journal of Research in Orthopaedics, 2025)
Spondylodiscitis caused by Aspergillus fumigatus is rare, particularly in immunocompetent individuals. This case highlights a unique instance of post-COVID Aspergillus spondylodiscitis, emphasizing the potential role of COVID-19-related immune dysregulation in predisposing patients to opportunistic fungal infections. A 75-year-old man with a history of hypertension, hypothyroidism, and severe COVID-19 (requiring ICU admission and steroid therapy) presented with chronic low back pain and acute bilateral lower limb weakness. Imaging revealed L1-L2 disc space narrowing, vertebral destruction, and epidural compression. Histopathological and microbiological analyses confirmed Aspergillus fumigatus infection. The patient underwent surgical decompression, debridement, and posterior stabilization, followed by intravenous voriconazole therapy, resulting in significant clinical improvement. This case underscores the importance of considering fungal etiologies in spondylodiscitis, especially in post-COVID patients with persistent symptoms. A multidisciplinary approach involving radiological, microbiological, and histopathological evaluation is critical for timely diagnosis and management. Combined surgical and antifungal therapy yielded favorable outcomes, aligning with existing literature recommendations. Further research is needed to explore the link between COVID-19 and opportunistic fungal infections.